Distant flap transfer with the vascular pedicle section in second stage - Rodrigo Pimenta Sizenando (Revista Brasileira de Cirurgia Plástica)
Introduction: Occasionally, there is no possibility of covering a wound with local grafts or flaps. This study aimed to evaluate the capacity of the distant flap transfer with the vascular pedicle section in second stage to cover the region that suffered substance loss. Methods: Five patients with substance loss, with no reconstruction option using grafts or local flaps, had their wounds covered by distant flap transfer with the vascular pedicle section in second stage. Results: The transferred flaps were useful in covering the wounds. Conclusion: distant flap transfer with the vascular pedicle section in second stage is a simple and effective procedure. Every plastic surgeon must master that.